Exploring the mechanisms of phishing. Issue 11 (November 2021) - Kaushik, Keshav; Singh, Sahajpreet; Garg, Saksham; Singhal, Sarthak; Pandey, Shambhavi
Abstract : Social engineering can be defined as a form of attack involving human interactions. 1, 2 It is used to force users or victims to make psychological mistakes so that they end up making a security mistake, giving up crucial information. Social engineering is about tricking users with the help of fake websites that look the same as legitimate ones or impersonating someone trustworthy, and it includes activities such as exploiting normal human behaviours like kindness and greed. Human behaviour is such that people tend to fall easily for anything they think is free, or anything they see as trustworthy.